Method for enhancing the bond exchange rate of bond exchange crosslinked resin by adding a small amount of ionic liquid

JP7635516B2Active Publication Date: 2025-02-26TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020132989
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-05
Publication Date
2025-02-26
Estimated Expiration
2040-08-05

Smart Images

  • Figure 0007635516000001
    Figure 0007635516000001
  • Figure 0007635516000002
    Figure 0007635516000002
  • Figure 0007635516000003
    Figure 0007635516000003
Patent Text Reader

Abstract

To provide a bond-exchange rate promotion method that adds a trace amount of ionic liquid to a bond-exchangeable dynamic covalent bond crosslink resin by transesterification, to affect the bond-exchange reaction, achieving a significant increase in the bond-exchange rate.SOLUTION: Regarding a bond-exchangeable resin by transesterification, a trace quantity of ionic liquid is added to the base composition of the bond-exchangeable resin, to promote the transesterification rate. The ionic liquid preferably should have a concentration of 0.1 wt.%-3 wt.% and should be a combination of organic cations and organic anions.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for promoting the bond exchange rate of a bond exchange crosslinked resin by adding a small amount of an ionic liquid. [Background technology]

[0002] Thermosetting resins that have undergone cross-linking reactions via covalent bonds are generally unable to be remolded or have surface scratches repaired. On the other hand, recently, thermosetting resins that use dynamic covalent bonds of the bond exchange type at the cross-linking points have been reported.

[0003] Such resins have the property that cross-linking bonds are exchanged at high temperatures, and therefore can be remolded, thinned, and have surface scratches repaired. The inventors of the present invention have already disclosed polyester resins having such properties in Japanese Patent Application No. 2020-83386.

[0004] Currently, efforts are being made to adjust the bond exchange activation temperature and bond exchange rate for bond exchange dynamic covalent cross-linked resins. In particular, if the time rate of bond exchange can be shortened, it will be possible to express useful functions such as remolding processability and repairability in a shorter time.

[0005] Non-Patent Document 1 describes bond exchange crosslinking based on transesterification using polyester as a constituent polymer. Non-Patent Document 2 describes the preparation of a bond exchange crosslinkable material based on transesterification. Neither document describes the shortening of the bond exchange rate by adding a small amount of ionic liquid. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Mikiho Hayashi, et al., Polymer Chemistry.10(16) 2047-2056, 2019 [Non-Patent Document 2] Ludwik Leibler, et al., Science. 334, 965-968, 2011 Summary of the Invention [Problem to be solved by the invention]

[0007] If the time rate of bond exchange could be shortened, it would be possible to achieve useful functions such as remolding and repairability in a shorter time, but the general method for achieving this is to reduce the crosslink density. However, reducing the crosslink density leads to problems such as a decrease in the material strength and heat resistance of the resin. Therefore, an object of the present invention is to provide a method for promoting the bond exchange rate of a bond exchangeable dynamic covalent bond cross-linked resin using an ester exchange reaction, which can affect the bond exchange reaction and significantly increase the bond exchange rate without affecting the material strength and heat resistance. [Means for solving the problem]

[0008] (1) A method for accelerating a bond exchange rate for a bond exchange crosslinking resin produced by an ester exchange reaction, comprising the step of: incorporating a trace amount of ionic liquid in the raw material composition of the bond exchange crosslinking resin to accelerate the ester exchange reaction rate. (2) The method for promoting a bond exchange rate according to (1), wherein the concentration of the ionic liquid contained in the raw material composition is 0.1 wt % to 3 wt %. (3) The method for promoting a bond exchange rate according to (1) or (2), wherein the ionic liquid is a salt (molten salt) that is composed of a cation and an anion and is liquid at room temperature and normal pressure. (4) The method for promoting a bond exchange rate according to (3), characterized in that the salt (molten salt) is liquid at room temperature and normal pressure and is composed of the cation and anion according to claim 3, and is any one of ionic liquids combining an organic cation composed of a quaternary imidazolium, a quaternary pyrrolidinium, a quaternary pyridinium, or a quaternary phosphonium with an organic anion composed of hexafluorophosphate, tetrafluoroborate, bistrifluoromethanesulfonylimide, triflate, or a halogen. (5) The method for promoting a bond exchange rate according to (4) above, wherein the ionic liquid is 1-Butyl-3-methylimidazolium Bis(trifluoromethanesulfonyl)imide, 1-Ethyl-3-methylimidazolium Tetrafluoroborate, 1-Butyl-3-methylimidazolium Hexafluorophosphate, or the like. (6) The method for accelerating a bond exchange rate according to any one of (1) to (5), wherein the raw material composition contains a hyperbranched thiol-terminated polyester, a diepoxy compound, an ester exchange catalyst, and an ionic liquid, and the raw material is heated to obtain a crosslinked resin. (7) The method for promoting a bond exchange rate according to (6), wherein the ratio of the thiol groups contained in the multibranched thiol-terminated polyester to the epoxy groups contained in the diepoxy compound is such that the thiol groups:epoxy groups of the epoxy crosslinking agent is 1:0.5 to 1:1.5. Effect of the Invention

[0009] In the polymer material (polyester thermosetting resin) according to the present invention, the addition of a small amount (for example, 1 wt%) of ionic liquid has the effect of significantly increasing the bond exchange rate at high temperatures compared to when no ionic liquid is added. [Brief description of the drawings]

[0010] [Figure 1]FIG. 1 is a schematic diagram of a method for synthesizing a polyester thermosetting resin that realizes a bond exchange rate acceleration method, which is one embodiment of the present invention, showing the compounds used in the synthesis and a synthesis scheme. [Diagram 2] FIG. 1 is a diagram showing the appearance (high transparency) of Example 1. [Diagram 3] FIG. 1 is a diagram showing the mechanism for improving the catalytic efficiency of an ionic liquid (inorganic catalyst). [Figure 4] FIG. 2 is a graph showing the temperature dependence of storage modulus (E′) and loss tangent tan δ for Example 1 and Comparative Example 1. [Diagram 5] FIG. 2 is a graph showing the results of stress relaxation measurements at 180° C. for Example 1, Comparative Example 1, and Comparative Example 2. [Figure 6] FIG. 2 is a graph showing the relationship between relaxation time and temperature obtained by stress relaxation measurement at 170° C. / 180° C. / 200° C. for Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. The present invention is not limited to the following embodiments, and changes, modifications, and improvements can be made without departing from the scope of the invention.

[0012] The compounds used in the synthesis and an outline of the synthesis scheme are shown in Figure 1. The raw material composition is composed of these compounds. Trimethylolpropane Tris(3-mercaptopropionate)(Tri-SH) was used as the trifunctional ester bond-containing compound (A), and Bisphenol A diglycidyl ether(Di-epoxy) was used as the diepoxy compound (B). These react with high efficiency by a click reaction between thiol and epoxy in the presence of a catalyst. Tin(II) 2-ethylhexanoate was used as the reaction catalyst (C). Note that tin(II) 2-ethylhexanoate also acts as an ester exchange catalyst. In addition to these, 1-Butyl-3-methylimidazolium Bis(trifluoromethanesulfonyl)imide(BMIM TFSI), an ionic liquid (IL), was added.

[0013] Tri-SH and Di-epoxy were weighed out so that the ratio of thiol to epoxy was 1:1, and 2-ethylhexanoate (II) and BMIM TFSI were added and mixed at room temperature until uniform. 2-ethylhexanoate (II) was 5 mol% relative to the thiol group. BMIM TFSI was 1 wt% of the total weight. In other words, BMIM TFSI in the raw material composition was 1 wt%. A Teflon (registered trademark) mold with a diameter of 9 cm was used for mixing. The reaction was carried out in an oven at 120°C for 12 hours (Example 1).

[0014] After the reaction, a colorless and highly transparent crosslinked sample (polyester thermosetting resin) was obtained (Example 1, thickness 1 mm). As shown in FIG. 2, even when the crosslinked sample 11 (Example 1) was placed on a white paper with "NITech" written in black letters, the letters "NITech" were as clear as the part where the sample was not placed. As a result of the swelling test using tetrahydrofuran, the unreacted material ratio (sol component) was almost 0%. For comparison, a crosslinked sample was prepared by adding only 2-ethylhexanoate (II) and carrying out the same reaction without adding BMIM TFSI (Comparative Example 1). In addition, a sample was also prepared by adding 1 wt% BMIM TFSI without adding 2-ethylhexanoate (II) and crosslinking (Comparative Example 2).

[0015] The reason why a polyfunctional ester bond-containing compound is used is that a one-pot preparation is possible because a crosslinking reaction proceeds with polymerization, and an ester exchange reaction can proceed within the network by including an ester bond. In addition, the functional group of the polyfunctional ester bond-containing compound is preferably a thiol group because a click reaction with an epoxy group (click reaction: a reaction that reacts with a conversion rate of almost 100% under reaction conditions with an equimolar amount) proceeds, and a sample can be prepared with a high yield. Other than the thiol group, there are carboxylic acid groups and amino groups. This is from the viewpoint of reactivity with an epoxy group. As the polyfunctional ester bond-containing compound, from the viewpoint of preparation efficiency that allows polymerization and crosslinking to proceed simultaneously, a trifunctional (3-branched), tetrafunctional (4-branched), or hexafunctional (6-branched) ester bond-containing compound is preferable, and a trifunctional ester bond-containing compound is particularly preferable.

[0016] On the other hand, 1,4-butanediol diglycidyl ether, 1,7-octadiene diepoxide, etc. may be used as the polyfunctional epoxy compound. This is from the viewpoint of reactivity with thiol groups, etc., as the polyfunctional epoxy compound. In addition, the transesterification catalyst is preferably a tin compound from the viewpoint of transparency, uniformity, and colorability of the shape-memory crosslinked polyester resin.

[0017] From the viewpoint of crosslinking efficiency, the ratio of the thiol groups contained in the multibranched thiol-terminated polyester to the epoxy groups contained in the diepoxy compound is preferably such that the thiol groups:epoxy groups of the epoxy crosslinking agent=1:0.5 to 1:1.5, and more preferably such that the thiol groups:epoxy groups of the epoxy crosslinking agent=1:0.75 to 1:1.25.

[0018] From the viewpoint of thermal stability and bond exchange promotion effect, the ionic liquid is preferably a compound having a high boiling point and a low melting point. In addition, the ionic liquid is preferably a salt (molten salt) composed of a cation and an anion and being liquid at room temperature and normal pressure. Specifically, any one of ionic liquids in which an organic cation composed of quaternary imidazolium, quaternary pyrrolidinium, quaternary pyridinium, or quaternary phosphonium, such as 1-Butyl-3-methylimidazolium Bis(trifluoromethanesulfonyl)imide, 1-Ethyl-3-methylimidazolium Tetrafluoroborate, or 1-Butyl-3-methylimidazolium Hexafluorophosphate, and an organic anion composed of hexafluorophosphate, tetrafluoroborate, bistrifluoromethanesulfonyl imide, triflate, or halogen are combined is preferable.

[0019] The concentration of the ionic liquid contained in the raw material composition is preferably 0.1 wt % to 3 wt %, and more preferably 0.5 wt % to 2 wt %, from the viewpoint of the mechanical properties and thermal properties of the resin resulting from mixing.

[0020] Figure 1 also shows the design of the polyester thermosetting resin (1) produced to realize the bond exchange rate acceleration method of the present invention. The polyester thermosetting resin (1) includes a polymer backbone containing multiple ester bonds (2) and free OH groups (3), multiple covalent bond crosslinking moieties (7) containing thioether crosslinking points (4), an ester exchange catalyst (5), and an ionic liquid (6). The free OH group (free hydroxyl group) (3) is a hydroxyl group that has not reacted with any functional group.

[0021] As shown in Figure 1(G), a transesterification reaction occurs when a free OH group (3) attacks the C-0 bond of one of the many ester bonds in the vicinity due to the action of a transesterification catalyst (5) present nearby. Figure 1(F) shows a schematic diagram of the epoxy ring-opening reaction between a thiol group and an epoxy group.

[0022] On the other hand, Figure 3 shows the improvement in catalytic efficiency of the transesterification catalyst of ionic liquid (6). The increase in the bond exchange rate is thought to be due to the fact that a trace amount of ionic liquid increases the dielectric constant of the system, which in turn reduces the activation energy of the transition state (H) of the bond exchange reaction in the transesterification reaction formula (1) (the increase in the dielectric constant of the system also enhances the interaction between the inorganic transesterification catalyst and the bond exchange reactive functional group).

[0023] (Temperature dispersion viscoelasticity measurement) A strip sample with a width of 4 mm, a thickness of 0.5 mm, and a length of 20 mm was obtained from the crosslinked sample (polyester thermosetting resin) by the synthesis method of Example 1. The temperature dispersion viscoelasticity of the strip sample was measured in the range of -50°C to 180°C using a DMS6100 (HITACHI High Tech). The measurement was performed in an N2 gas atmosphere at a temperature change rate of 5°C / min. The measurement frequency was 20Hz, and the strain was 0.1%.

[0024] FIG. 4 shows the temperature dependence of storage modulus (E') and loss tangent tanδ. A tanδ peak (α relaxation peak) due to segment relaxation is seen at about 45°C. The sample is in a glassy state at lower temperatures than this peak region, and in a rubbery state at higher temperatures. The α relaxation peak temperature and rubbery plateau modulus were almost the same for the sample with ionic liquid (Example 1) and the sample without ionic liquid (Comparative Example 1). From these results, it can be confirmed that the addition of 1 wt% ionic liquid has almost no effect on the network structure inside the sample.

[0025] (Stress relaxation test) The stress relaxation was measured at 170°C, 180°C, and 200°C using MCR302 (Anton Paar) for the sample with ionic liquid (Example 1), the sample without ionic liquid (Comparative Example 1), and the sample without catalyst (Comparative Example 2). All measurements were performed in a N2 gas atmosphere.

[0026] FIG. 5 shows the results of stress relaxation measurements at 180° C. for Example 1, Comparative Example 1, and Comparative Example 2. The vertical axis shows stress (σ) normalized by the initial stress (σ0), and the horizontal axis shows the elapsed time. Sufficient stress relaxation was observed in Example 1 and Comparative Example 1, while almost no stress relaxation was observed in Comparative Example 2. This result shows that BMIM TFSI has almost no effect as a transesterification catalyst. Comparing Example 1 and Comparative Example 1, it can be seen that Example 1, which contains BMIM TFSI, has a faster relaxation rate, and it can be seen that the addition of BMIM TFSI contributes to the catalytic activity.

[0027] FIG. 6 shows the relationship between the relaxation time and temperature obtained by stress relaxation measurements at 170°C, 180°C, and 200°C for Example 1 and Comparative Example 1. The relaxation time was determined as the time when the initial stress became 1 / e times (about 0.37 times) assuming the Maxwell model. It was found that Example 1 containing BMIM TFSI had a faster relaxation rate at all temperatures. For example, the addition of 1 wt% BMIM TFSI increased the bond exchange rate by about three times at 180°C. These results suggest that the presence of an ionic liquid in the system improves the catalytic efficiency of the inorganic catalyst. [Industrial Applicability]

[0028] The ability of the ionic liquid used in the present invention to increase the bond exchange rate has not been found so far, and this makes it novel and highly applicable as a new function and application of ionic liquids. [Explanation of symbols]

[0029] 1, 11: Polyester thermosetting resin (crosslinked resin) 2: Ester bond 3: Free OH group 4: Bridge branch point 5: Transesterification catalyst 6: Ionic liquid

Claims

1. Regarding crosslinked polyester resins capable of ester bond exchange using ester exchange reaction, A method for accelerating a bond exchange rate, comprising the step of: incorporating 0.1 wt % to 3 wt % of an ionic liquid and an ester exchange catalyst (excluding those that become ionic liquids) in the raw material composition of the crosslinked polyester resin to accelerate the ester exchange reaction rate.

2. 2. The method for promoting bond exchange rate according to claim 1, wherein the ionic liquid is a salt (molten salt) composed of cations and anions and which is liquid at room temperature and normal pressure.

3. A method for promoting bond exchange rate, characterized in that the salt (molten salt) which is liquid at room temperature and normal pressure and which is composed of a cation and an anion as described in claim 2 is composed of any one of ionic liquids which combine an organic cation composed of a quaternary imidazolium, a quaternary pyrrolidinium, a quaternary pyridinium, or a quaternary phosphonium with an organic anion composed of hexafluorophosphate, tetrafluoroborate, bistrifluoromethanesulfonylimide, triflate, or a halogen.

4. The ionic liquid according to claim 3 is 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, or 1-butyl-3-methylimidazolium hexafluorophosphate.

5. The method for accelerating a bond exchange rate according to any one of claims 1 to 4, characterized in that the raw material composition contains a hyperbranched thiol-terminated polyester, a diepoxy compound, an ester exchange catalyst, and an ionic liquid, and the raw material is heated to obtain a crosslinked polyester resin.

6. The ratio of the thiol group contained in the multi-branched thiol-terminated polyester to the epoxy group contained in the diepoxy compound is 6. The method for promoting a bond exchange rate according to claim 5, wherein the thiol group:the epoxy group=1:0.5 to 1:1.5.

Citation Information

Patent Citations

  • Method for producing glycerol carbonate

    JP2019505528A

  • Soft crosslinked polyester resin / film exhibiting self-adhesive property, re-formability, and flaw-repairing property, and production method therefor

    WO2020045439A1

  • Composite material derived from lignocellulose biomass and method for producing same

    WO2020045510A1